Structural and Electrical Investigation of MoS2 Thin Films Formed by Thermal Assisted Conversion of Mo Metal. (1st January 2016) - Duffy, Ray; Foley, Patrick; Filippone, Bruno; Mirabelli, Gioele; O'Connell, Dan; Sheehan, Brendan; Carolan, Pat; Schmidt, Michael; Cherkaoui, Karim; Gatensby, Riley; Hallam, Toby; Duesberg, Georg; et al.
Abstract : Large-area synthesis is of great demand for the preparation of high-performance transition-metal-dichalcogenides (TMD) devices, however there are only limited reports to date of device operation on large-area TMDs. In this work we fabricate MoS2 devices based on Thermal Assisted Conversion (TAC) of metal layers, and characterize the thin-films with material analysis combined with electrical device parameter extraction. Specifically we report on temperature dependent parameter extraction for Ti/Au contacts to MoS2 thin-films to determine sheet resistance (Rsh ), resistivity (ρ), and the activation energy (EA ) of on-state current flow. For undoped MoS2, ρ was determined to be 191 Ω.cm at 25°C. The activation energy of the on-state current was found to be 0.18 eV, pointing to the presence of deep levels in MoS2 .